Literature review on the evolutional steps in updating Gleason grading system of prostatic adenocarcinoma - Abo Dega, Farah (Karbala Journal of Medicine, 2020)
The evolution of the famous original grading system for prostatic adenocarcinoma which initially described by Dr. Donald Gleason in the 1960s–1970s passed through two steps of modifications according to two major consensus meetings achieved by the International Society of Urologic Pathology (ISUP) in 2005 and 2014 respectively according to many researches and clinical trials to be finely incorporated into the recent World health organization (WHO) classification of prostate cancer and staging system as one of the powerful prognostic factor and treatment decision factor .This articles briefly review historical aspects of the original Gleason grading system and the recent modifications , describing the major changes over the years that finely resulted in the contemporary Gleason grading system, which proposed a new “Grade Group” system established by the 2014 ISUP meeting , and then incorporated to the recent ( 2016) WHO classification of tumors of the prostate.